Comparative evaluation of two porcine ex vivo models for training in endoscopic ultrasound-guided drainage of pancreatic fluid collections - Moryoussef, Frederick; Leblanc, Sarah; Bertucat, Alice; Laquiere, Arthur; Coron, Emmanuel; Mangialavori, Luigi; Duchmann, Jean-Christophe; Le Baleur, Yann; Prat, Frederic (Endoscopy International Open, 2017)
Introduction EUS-guided cystoenterostomy (EUCE), a technique used for the drainage of pancreatic pseudocysts and peri-enteric collections, requires specific skills for which dedicated models are needed. Based on a compact EASIE model (Erlangen Active Simulator for Interventional Endoscopy), we developed two ex vivo porcine models of retrogastric cysts and evaluated learning performance within the frame of a structured training program.Material and methods The first model was made of porcine colon (i. e. “natural cyst”), the second one with an ostomy bag (i. e. “artificial cyst”). All procedures were achieved with an EUS scope under fluoroscopy. Both models were evaluated prospectively over a 2-day session involving 14 students and five experts. The primary end point was overall satisfaction with each model.Results The “natural cyst” and “artificial cyst” were prepared within 10 and 16.5 minutes (P = 0.78), respectively. Model grading showed a non-significant trend for overall satisfaction in favor of the artificial model (P = 0.06). As secondary end points, difference was not significant for impression of realism (P = 0.75) whereas the “artificial cyst” was graded significantly better by experts and students in terms of ability to teach procedural steps (P = 0.01) and ease of puncture (P = 0.03). Moreover, experts considered the ability to improve students’ proficiency to be superior with the “artificial cyst” (P = 0.008).Conclusion Both “artificial” and “natural cysts” are efficient for EUCE training in terms of overall satisfaction. However, the “artificial cyst” model appears to make the procedure easier with a higher ability to teach procedural steps and improve the students’ proficiency. Larger applications of this model are needed to validate as a standard of training.